Morphological features of fat tissue of epiploon and subcutaneous fat tissue in patients with overweight and metabolic syndrome. - K. M. Militsa; I. V. Sorokina; M. S. Myroshnychenko; O. N. Pliten (Морфологія, 2015)
Background. Integrated clinical and morphological studies of adipose tissue in overweight and obese patients with metabolic syndrome in order to identify its morphological and functional characteristics can help to improve current methods of treatment. Objective. The purpose of the study was to identify the histological, histochemical and morphometrical characteristics of adipose tissue in patients with overweight and metabolic syndrome. Methods. The material of this study was the autopsy and operational material – fat tissue of epiploon and subcutaneous fat tissue. The authors used histological, histochemical and morphometrical methods of investigation. Results. It was revealed that fat tissue of epiploon and subcutaneous fat tissue in patients with overweight and metabolic syndrome differed from the fat tissue of people with normal body weight by morphometrical parameters, fat content in the cytoplasm, sclerotic changes, circulatory disorders, the presence and character of inflammatory infiltration. Moreover fatty tissue has distinctive features depending on the location. Conclusion. Observed morphological features of white fat tissue of epiploon and subcutaneous fat tissue in patients with overweight and metabolic syndrome can be used by pathologists, histologists and other specialists in the scientific practice.